Associated Injuries in Patients with Maxillofacial Trauma at Dhaka Dental College Hospital by Motorcycle Accident - Abedin, Md Zahir; Sultana, Farjana; Haider, Ismat Ara; Islam, Mohammed Rahatul; Towhid , Sarwar Jahan Towhid; Islam, Md Shahadul (Update Dental College Journal, 2023)
Background: Facial skeleton injuries are common in emergency departments and can cause physical and psychological distress. The mandible is the most commonly fractured site, followed by the maxillae, zygomatic bone, and nasal bone. Tooth injuries are also common. Although rarely fatal, these injuries may be associated with life-threatening conditions in other parts of the body. Objective: To assess the other bony and soft tissue injuries along with facial bone fracture Methods: It was a cross-sectional observational study carried out in the Department of Oral and Maxillofacial Surgery, Dhaka Dental College and Hospital. Main outcome variable were age, sex, site, etiology, bony and soft tissue injury over the skin. Thirty patients with maxillofacial trauma who were attended to the Department of Oral and Maxillofacial Surgery were selected for the study. Study Period: 10 January 2019 to 15 July 2019 Results: Majority of the patients were in the 2nd to 4th decade (80%) with a male to female ratio of 6.5:1. The motorcycle accident occurred with pavement 9 (30.0%) followed by 20% with truck, 5 (16.7%) with bus, 13.3% with motorcycle, 10% accident with pedestrian and 6.7% with autorickshaw. Mandible was the most commonly fractured facial bone (36.67%), followed by midface fracture (20.0%), Lefort-II (16.7%) and Lefort-III (13.3%). Closed head injury such as scalp injury were more 19 (63.3%) then linear fracture 7 (23.3%) and depressed fracture of temporal bone. A total of 23 (76.7%) patients were wearing a helmet at the time of the accident and rest of 7 (23.3%) had no helmet. The soft tissue injuries were significantly more in non-helmeted subjects (p< 0.05). Non-helmet subjects sustained more injuries as compared to helmeted subjects. The injuries were significantly more in non-helmet motorcyclists Conclusion: The study found that males aged 21-40 were most commonly injured in motorcycle accidents, with motorcycle riders and rideshare businessmen being the largest groups of victims. Midface fractures were the most common facial injury and were significantly associated with helmet use. Protective gear was found to be low among motorcycle riders, particularly passengers, impacting the severity of injuries sustained. Update Dent. Coll. j: 2023; 13(2): 30-33